2017
DOI: 10.1155/2017/7834035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL-18 and IL-10 Polymorphisms on Tacrolimus Elimination in Chinese Lung Transplant Patients

Abstract: Aims. The influence of interleukin-10 (IL-10) and interleukin-18 (IL-18) polymorphisms on tacrolimus pharmacokinetics had been described in liver and kidney transplantation. The expression of cytokines varied in different kinds of transplantation. The influence of IL-10 and IL-18 genetic polymorphisms on the pharmacokinetic parameters of tacrolimus remains unclear in lung transplantation. Methods. 51 lung transplant patients at Shanghai Pulmonary Hospital were included. IL-18 polymorphisms (rs5744247 and rs194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
(39 reference statements)
3
9
0
Order By: Relevance
“…The frequency of CYP3A5*3 variant differs among world populations, which is estimated to be 94, 68-71 and 18% in Europeans, Asians, and Africans, respectively [6]. The mutation rate in this study was 73%, comparable to previous studies in Chinese transplant recipients [16,18].…”
Section: Statement Of Key Ndingssupporting
confidence: 74%
See 2 more Smart Citations
“…The frequency of CYP3A5*3 variant differs among world populations, which is estimated to be 94, 68-71 and 18% in Europeans, Asians, and Africans, respectively [6]. The mutation rate in this study was 73%, comparable to previous studies in Chinese transplant recipients [16,18].…”
Section: Statement Of Key Ndingssupporting
confidence: 74%
“…In LTx, similar results have been reported in Caucasians [12][13][14]. But studies in Chinese population are limited till now [15,16], and Chinese has a different mutation rates of CYP3A5*3 from Caucasians [6], so, there is a major void in this research area.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…One prominent example relates to the rs1946518 (-607C/A) variant within the promoter of IL-18 and its effects on the metabolism of the immunosuppressive tacrolimus. Xing et al and Zhang et al demonstrated that Han-Chinese patients carrying the AA genotype (19–29% of the patients) exhibited lower concentration/dose (C/D) ratios of tacrolimus within the first month after lung or kidney transplantation than patients with an AC or CC genotype [ 87 , 88 ]. Interestingly, this relationship for the rs1946518 variant was exclusively shown for patients expressing CYP3A5*1 and functionally linked to lower expression of IL-18 mRNA in the liver.…”
Section: Pharmacogenetic Variation In Inflammatory Pathways and Thmentioning
confidence: 99%
“…Except for a different frequency of CYP3A5*3 allele from Caucasians, males and older recipients seems to account for the majority of Chinese LTx population [10,11]. Till now, studies in this population are limited and usually conducted in small sample sizes, leaving a major void in this area [12,13].…”
Section: Introductionmentioning
confidence: 99%